Prisoner of the state : the secret journal of Zhao Ziyang - Zhao, Ziyang; Bao, Pu, 1967?; Chiang, Renee; Ignatius, Adi.; MacFarquhar, Roderick (New York : Simon & Schuster, 2009)
Gives readers a front row seat to the secret inner workings of China's government. It is the story of Premier Zhao Ziyang, who tried to stop the Tiananmen Square massacre in 1989, and was dethroned for his efforts.
The Tiananmen massacre. The student protests begin ; An editorial makes things worse ; Power struggle ; The crackdown ; The accusations fly ; The campaign against Zhao ; Zhao's talk with Gorbachev -- House arrest. Zhao becomes a prisoner ; The investigative report ; Zhao's lonely struggle -- The roots of China's economic boom. Conflicting views at the top ; An early setback ; Opening painfully to the world ; Finding a new approach ; Zhao and Hu clash ; Playing a trick on a rival ; One step at a time ; The economy gets too hot ; The magic of free trade ; Freedom on the farm ; The coastal regions take off ; Coping with corruption -- War in the Politburo. Hu Yaobang "resigns" ; Zhao walks the line ; The ideologues ; Preparing for the main event -- A tumultuous year. After the Congress ; Panic buying and bank runs ; A series of missteps ; The problem with prices ; Reforms take a hit ; Zhao in retreat ; The campaign to overthrow Zhao -- How China must change. Deng's view on political reform ; Hu's view on political reform ; How Zhao's view evolved ; The old guard fights back ; The way forward -- A brief biography of Zhao Ziyang.
Keywords: Zhao, Ziyang; Zhao, Ziyang; Prime ministers -- China -- Biography; Political prisoners -- China -- Biography; Statesmen -- China -- Biography; China -- Politics and government -- 1976-2002.; China -- History -- Tiananmen Square Incident, 1989.